Correlation Between Delivery Type and Pelvic Floor Dysfunction: A Case-Control Study - Azar Danesh Shahraki; Maryam Hajhashemi; Minoo Movahedi; Fatemeh Abbasi (Advanced Biomedical Research)
Background: Mode of delivery is associated with pelvic floor dysfunction (PFD). Therefore, this study aimed to investigate the relationship between delivery type and PFD six-month after delivery. Materials and Methods: This case-control study included primigravida females who had a normal vaginal delivery with episiotomy (VDE) or uncomplicated cesarean section. All participants underwent an evaluation to check the strength and endurance of the pelvic floor muscles (PFM), intravaginal pressure measurement, electromyographic activity recording of the PFM, and Pelvic Floor Distress Inventory-20 (PFDI-20) questionnaire. Results: In total, 260 patients were enrolled in our study and divided equally into two groups: uncomplicated cesarean delivery and VDE. Our findings showed significant differences in PFM dysfunction, electrical activity, strength, endurance, and vaginal pressure between the two groups. Patients who underwent an uncomplicated cesarean delivery had better outcomes. Conclusion: Our study demonstrated that the severity of PFD in women who underwent uncomplicated cesarean section was lower than that in women who underwent VDE. VDE may cause PFM injury.